Flow induced by a constantly accelerating edge in a Maxwell fluid - Fetecau, C.; Fetecau, C. (Archives of Mechanics, 2004)
The paper deals with the flow induced by a constantly accelerating edge in a Maxwell fluid. The solutions obtained satisfy both the associate partial differential equations and all imposed initial and boundary conditions. For λ → 0 they reduce to those corresponding to a Navier-Stokes fluid.